Constructing legitimation in Scottish newspapers: The case of the independence referendum. (December 2019) - Alonso-Almeida, Francisco; Luisa Carrió-Pastor, María
This study is concerned with the use of epistemic legitimising strategies in online newspaper articles dealing with the Scottish referendum. In this sense, we seek to explore cases of epistemic stance that indicate epistemological positioning and persuade readers of the veracity of propositions. Our study covers Scottish journal articles published online within 5 days prior to results day. In this article, we are interested in the way the Scottish newspapers deal with the topic of the independence referendum and the degree of commitment in journalists' choice of linguistic strategies. We analysed the newspaper articles manually but corpus tools were also used in order to verify initial findings and for statistical purposes. The results of the use of epistemic stance devices in the different categories were contrasted and our conclusions showed the preferred legitimising strategies used by journalists in the Scottish newspapers.